Borges y la crítica de arte en Mallorca (1920-1921) - García, Carlos (Huarte de San Juan. Filología y Didáctica de la Lengua, 2013)
These notes deal with an unusual chapter of Borges’ insertion in the Spanish avant-garde, more specifically in the Mallorcan avant-garde, from which Borges was one of the leaders. Part of the information contained herein comes from a previous work, originally published under the title «Borges y las artes plásticas. En torno a un texto casi desconocido: Contra crítica» in Variaciones Borges 2, Aarhus, June 1996, 188-191, there with some minor errors and omissions. A shorter version without intermingled commentaries appeared in Letras de Buenos Aires 34, July 1996, 19-21 («Contra crítica. Un texto desconocido de Borges»). That work, which was published before the appearance of Textos recobrados, 1919-1929 (1997), emphasized on Borges’ text, which was unknown in Argentina at that moment, except perhaps for some specialists. The present work has another purpose: to place the text of Borges in a broader context – namely that of art criticism in Mallorca 1920-1921.
Keywords: Borges; spanish avant-garde; art criticism